INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM MENINGKATKAN KECERDASAN SPIRITUAL PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA BAHRUL MAGHFIROH MALANG - Tommy Saputra; Muhammad Hanif; Indra Musthofa (VICRATINA, 2021)
The process of cultivating character values has a big role in shaping the identity and behavior of students, but this is influenced by environmental conditions, so that when the environment is encountered by students brings good things, of course habits with these good things can form values. character values in students, planting these character values will be implemented more quickly. This research uses a descriptive qualitative approach. This type of research is a case study. Data collection was carried out by observation, interviews, and documents. To analyze the data that has been obtained using qualitative analysis from Miles and Haberman, namely through Data Reduction, Data Presentation, and Conclusion Drawing. Internalization of Character Values in Improving the Intelligence of Students in Bahrul Maghfiroh Junior High School, Malang City, including habits, praying dhuha, and reading the Koran which has become a culture in this school.